Unravelling socio-motor biomarkers in schizophrenia - Piotr Słowiński (Nature Portfolio, 2017)
Mirror game test could detect schizophrenia A new test of movement and social interaction could detect markers of schizophrenia, and help to diagnose and manage the condition. In an effort to establish reliable indicators of schizophrenia, Piotr Slowinski at the University of Exeter, UK and colleagues developed a test that could detect deficits in movement and social interactions, both characteristics of the disorder. They asked people to perform movements alone, and to mirror the movements of a computer avatar or a humanoid robot. Automated analysis of the movements allowed to distinguish people with schizophrenia from healthy participants with accuracy and specificity slightly better than clinical interviews and comparable to test based on much more expensive neuroimaging methods. The technique could help with diagnosis of schizophrenia and to monitor patients’ responses to treatment, but needs to be tested in clinical trials before being applied in clincal practice.